Kajian Penentuan Arah Kiblat Menggunakan Arah Planet Venus - Siti Anisa Hidayati, Siti Anisa Hidayati; Yushardi (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2023)
The purpose of this research is to find out how to determine the Qibla direction of aplace using the position of the planet Venus and how to prove the calculation of the position ofVenus in the sky. This research is motivated by the question of how to determine the Qibladirection at night if the conditions do not have sophisticated technological equipment. Thisresearch is a descriptive analysis research where all the data is collected through observationtechniques. The research results show that the position of the planet Venus can be used as analternative reference to determine the Qibla direction. Based on observations using astronomicalcalculations, it is known that Venus looks very luminous on the western horizon when the sky isclear and the sun has set perfectly. We can also see one of the planets Venus at dawn on theeastern horizon, so Venus is also often referred to as the morning star. Data on the position of theplanet Venus such as the altitude and azimuth of the planet Venus somewhere are then calculatedusing the horizon coordinate system. The data is used as a theodolite reference. Furthermore, toobtain the actual Qibla direction, the theodolite lens is directed to the position of the planet Venusand rotated clockwise (same as the difference in the azimuth angle with the Qibla azimuth ofVenus). Thus, the position of the planet Venus can be used as an alternative to determine the Qibladirection.